The Utility of Cranial Ultrasound for Detection of Intracranial Hemorrhage in Infants. Issue 2 (February 2018) - Elkhunovich, Marsha; Sirody, Joseph; McCormick, Taylor; Goodarzian, Fariba; Claudius, Ilene
Abstract : Objective: The objective of this study was to evaluate the sensitivity and specificity of cranial ultrasound (CUS) for detection of intracranial hemorrhage (ICH) in infants with open fontanels. Methods: This was a retrospective study of infants younger than 2 years who had a CUS performed for the evaluation of potential ICH. We excluded patient with CUSs that were done for reasons related to prematurity, transplant or oncologic evaluations, routine follow-up or preoperative screen, or congenital and known perinatal anomalies. Two clinicians independently classified each of the patients with ICH into significant or insignificant based on the radiology reports. Results: Of 4948 CUS studies performed during the 5-year study period, 283 studies fit the inclusion criteria. Patient age ranged from 0 to 458 days, with a median of 33 days. There were 39 total cases of ICH detected, with 27 significant bleeds and 12 insignificant bleeds. Using computed tomography, magnetic resonance imaging, or clinical outcome as criterion standard, the overall ultrasound sensitivity and specificity for bleed were 67% (confidence interval [CI], 50%–81%) and 99% (CI, 97%–100%), respectively. For those with significant bleeds, the overall sensitivity was 81% (CI, 62%–94%), and for those with insignificant bleeds, it was 33% (CI, 1%–65%). Conclusions: The sensitivity of CUS is inadequate to justify its use as a screening tool for detection of ICH in young infants.